MODERN POSSIBILITIES OF REMOTE MONITORING OF FETAL CONDITION - Репина, Екатерина Сергеевна; Костелей, Яна Валерьевна; Буреев, Артем Шамильевич; Жданов, Дмитрий Сергеевич; Юрьев, Сергей Юрьевич (Mother and Baby in Kuzbass, 2022)
Decreasing perinatal morbidity and mortality is modern obstetrics concern. However, the methods of monitoring fetus condition established in obstetrics can provide data about prenatal condition at the time of testing and do not have prognostic value. Therefore, early signs of prenatal hypoxia may be missed. The instrument which might resolve this issue is distant monitoring of fetus condition, meaning monitoring fetus outside the hospital and without medical specialists’ direct involvement. Apart from decreasing costs of hospital stay and decreasing medical personnel workload, this technology will let a pregnant woman monitor fetus condition anywhere and anytime. Moreover, using telehealth technologies is supposed to help a woman to get medical or technical help in real-time mode. Distant monitoring of fetus condition is an up-to-date sector of medical research. The methods currently being developed vary in terms of safety, effectiveness and cost. The present article reviews the methods of distant fetus condition monitoring currently being developed in the world.